PREPARACIÓN DE FILTROS DE ADSORCIÓN A BASE DE ARCILLAS MODIFICADAS - Sun Kou, María del Rosario (2019)
During the last years in Perú the amount of textile contamination (dyes, surfactants, phenols among others) has increased due to the increase in export volumes.Adsorption is one of the methods most often used to minimize the grade of contamination in industrial effluents, and it has encouraged the development of abundant materials wich are low cost and so they could be used as adsorbents. For this work has been used peruvian bentonites, sodium (LI-01 and LI-03) and calcium (HU-01 and HU-02), modified by thermo-activation with HCl and H2SO4. These materials were tested in the adsorption of several dyes: Red 80, Rhodamine B, Acid Red G, methylene blue. A sample of thermo-activated LI-03 increased its power of adsorption thirteen times compared with the natural clays, on the other hand in the case of HU-01 increase was eleven times. The adsorption process is produced in pH range of 3 - 4 when electrolytes were added into dye solution.The best method found for the preparation of filters of adsorption from thermo-activated clays was the polymer sponge with thermic treatment in the range of 500 - 980ºC. Prepared filters adsorbed 100% of dyes: Rhodamine B and Methylene Blue. The adsorption got in low degree with Red dye 80 and Acid Red G.